Alcohol-related liver disease (ALD): current perspectives on pathogenesis, therapeutic strategies, and animal models - Hong, Xiao; Huang, Shuo; Jiang, He; Ma, Qing; Qiu, Jiang; Luo, Qihan; Cao, Chunlu; Xu, Yiyang; Chen, Fuzhe; Chen, Yufan; Sun, Chunfeng; Fu, Haozhe; et al. (Frontiers in Pharmacology, 2024)
Alcohol-related liver disease (ALD) is a major cause of morbidity and mortality worldwide. It encompasses conditions such as fatty liver, alcoholic hepatitis, chronic hepatitis with liver fibrosis or cirrhosis, and hepatocellular carcinoma. Numerous recent studies have demonstrated the critical role of oxidative stress, abnormal lipid metabolism, endoplasmic reticulum stress, various forms of cell death (including apoptosis, necroptosis, and ferroptosis), intestinal microbiota dysbiosis, liver immune response, cell autophagy, and epigenetic abnormalities in the pathogenesis of ALD. Currently, abstinence, corticosteroids, and nutritional therapy are the traditional therapeutic interventions for ALD. Emerging therapies for ALD mainly include the blockade of inflammatory pathways, the promotion of liver regeneration, and the restoration of normal microbiota. Summarizing the advances in animal models of ALD will facilitate a more systematic investigation of the pathogenesis of ALD and the exploration of therapeutic targets. This review summarizes the latest insight into the pathogenesis and molecular mechanisms of ALD, as well as the pros and cons of ALD rodent models, providing a basis for further research on therapeutic strategies for ALD.